Artificial intelligence dalam Desain Arsitektur serta Kaitannya dalam aspek Ekonomi Berkelanjutan di Indonesia - Astri Puspita (Universitas Borobudur, 2023)
Advances in technology and digital systems are increasing rapidly, making work easier and faster. AI technology is able to hypnotize all people. With only voice, written and image commands, we can get the desired information. AI enters the realm of architectural design with its viral AI that is able to design without an architect. does this threaten the existence of architects and what about infrastructure development which is an instrument and a reflection of certain areas in sustainable economic progress in Indonesia. The method used is a systematic literature review with literature/journals/electronic databases according to topics in the last 10 years. The results show that the position of architects cannot be replaced with digital, because through a long and difficult design process and architectural products as economic instruments for certain regions related to the culture and wealth of the archipelago, they are not easily replaced by AI. But in the future, AI technology will be more advanced and developing rapidly, so strengthening human resources must also be strengthened so that humans remain in control of technology.